Soy-tomato enriched diet reduces inflammation and disease severity in a pre-clinical model of chronic pancreatitis - Debasmita Mukherjee (Nature Portfolio, 2020)
Abstract Chronic pancreatitis (CP) is a fibro-inflammatory syndrome in individuals who develop persistent pathological responses to parenchymal injury or stress. Novel therapeutic or dietary interventions that could lessen inflammation in this disease could significantly improve quality of life in patients with CP. Complex dietary foods like soy and tomatoes are composed of active metabolites with anti-inflammatory effects. Data from our group reports that bioactive agents in soy and tomatoes can reduce pro-inflammatory cytokines and suppressive immune populations. Additionally, our team has developed a novel soy-tomato juice currently being studied in healthy individuals with no toxicities, and good compliance and bioavailability. Thus, we hypothesize that administration of a soy-tomato enriched diet can reduce inflammation and severity of CP. C57BL/6 mice were injected intraperitoneally with 50 μg/kg caeurlein (7 hourly injections, twice weekly) for 6 weeks to induce CP. After 4 weeks of caerulein injections, mice were administered a control or a soy-tomato enriched diet for 2 weeks. Disease severity was measured via immunohistochemical analysis of pancreata measuring loss of acini, fibrosis, inflammation, and necrosis. Serum lipase and amylase levels were analyzed at the end of the study. Inflammatory factors in the serum and pancreas, and immune populations in the spleen of mice were analyzed by cytokine multiplex detection, qRT-PCR, and flow cytometry respectively. Infra-red (IR) sensing of mice was used to monitor spontaneous activity and distress of mice. Mice fed a soy-tomato enriched diet had a significantly reduced level of inflammation and severity of CP (p = 0.032) compared to mice administered a control diet with restored serum lipase and amylase levels (p < 0.05). Mice with CP fed a soy-tomato diet had a reduction in inflammatory factors (TNF-α, IL-1β, IL-5) and suppressive immune populations (myeloid-derived suppressor cells; MDSC) compared to control diet fed mice (p < 0.05). Infra-red sensing to monitor spontaneous activity of mice showed that soy-tomato enriched diet improved total activity and overall health of mice with CP (p = 0.055) and CP mice on a control diet were determined to spend more time at rest (p = 0.053). These pre-clinical results indicate that a soy-tomato enriched diet may be a novel treatment approach to reduce inflammation and pain in patients with CP.